Protective family regimen in cleft lip and palate - Cerný, M; Fára, M; Hrivnáková, J (Acta chirurgiae plasticae, 1989)
The Department of Plastic Surgery, Prague, provides comprehensive care to children and families where cleft lip and palate occur, which goes under the name of preventive family regimen. Apart from the treatment alone, this regimen is the concern of a number of specialists whose aim is to eliminate the parents' sense of "guilt", and to try, with the aid of the family, to create a situation which would improve the condition for the child's socialization. The geneticist is in charge of the prenatal preventive regimen which consists in the recommendation for the dated conception in an attempt to influence the baby's sex prior to conception, in eliminating potential internal and infectious (TORCH) etiological factors as well as potential teratogenic agents within the family. Gynecological care is aimed at uterine hypoplasia, atypia, gynaecological inflammation and hormonal deviations. Two months prior to conception and in the 1st trimester, it is recommended to keep to a diet rich in proteins, mineral substances, trace elements, vitamins and folic acid. The authors point to the potential risks of this method (impaired prenatal selection, increased fertility of risk families). At present, it is not possible to make an objective assessment of the results of the preventive pre-conception regimen due to the unrepresentative selection of the group under observation.
Keywords: Infant, Newborn; Cleft Palate; prenatální péče; Humans; Female; Cleft Lip; novorozenec; lidé; ženské pohlaví; těhotenství; rizikové faktory; rozštěp rtu; rodina; Československo; Czechoslovakia; Risk Factors; rozštěp patra; Pregnancy; Prenatal Care; Family